2015
DOI: 10.1111/jcmm.12580
|View full text |Cite
|
Sign up to set email alerts
|

Notch receptor expression in human brain arteriovenous malformations

Abstract: The roles of the Notch pathway proteins in normal adult vascular physiology and the pathogenesis of brain arteriovenous malformations are not well-understood. Notch 1 and 4 have been detected in human and mutant mice vascular malformations respectively. Although mutations in the human Notch 3 gene caused a genetic form of vascular stroke and dementia, its role in arteriovenous malformations development has been unknown. In this study, we performed immunohistochemistry screening on tissue microarrays containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Human brain AVMs have disrupted elastin fibers, which compromise the structural integrity of the vessel and mediate arteriovenous malformations 1921 . While brain elastin content has been well characterized, the elastin in extracranial vascular malformation has not been studied.…”
Section: Resultsmentioning
confidence: 99%
“…Human brain AVMs have disrupted elastin fibers, which compromise the structural integrity of the vessel and mediate arteriovenous malformations 1921 . While brain elastin content has been well characterized, the elastin in extracranial vascular malformation has not been studied.…”
Section: Resultsmentioning
confidence: 99%
“…Notch signaling pathway played a key role in liver homeostasis, metabolism, regeneration, vascular physiology, and reparative morphogenesis of the biliary tree . However, it was difficult to distinguish whether it was hepatocytes, biliary epithelial cells, or sinusoidal endothelial cells specificity of Notch signaling that played crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed an augmented expression of EphrinB2, Hey2 and Dll4 in the nidus structures from patients with cerebral AVM when compared to normal brain arteries. Previous studies have reported that Notch-1 and Notch-3 are over expressed in AVM nidus [ 32 34 ]. Together our findings suggest that a deregulated arterial specification signaling might have a significant role in the pathogenesis of AVM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had identified that endothelial cell of AVM vessels expresses either artery or vein marker [ 32 , 33 , 34 ]. Co-expression of both artery-specific genes HEY2 , DLL4 , EFNB2 and vein specific gene COUP-TFII in endothelial cells of AVM vessels as observed in our study is a novel finding.…”
Section: Discussionmentioning
confidence: 99%